2017
DOI: 10.4108/eai.28-6-2017.152748
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using social media and internet on academic performance case study Bahrain Universities

Abstract: The internet and social media provide students with a range of academic benefits and opportunities to enhance their learning process. The main goal of this research is to examine the impact of using the social media on the academic performance. The new social networks, such as Instagram, Facebook, Twitter, etc., can affect the behaviour and academic performance of the universities' students; therefore the selected universities were Ahlia University, Applied Science University and University of Bahrain. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Cankaya and Yunkul (2018) found in their study that WhatsApp is the most used social networking sites by participants in a mixed method study. Similarly, Abdulla (2017) also discovered that among other social networking sites like Twitter, Instagram, and Facebook, WhatsApp is the most preferred by university students. Besides, Ling (2016) and Yin (2016), both studies carried out in Malaysia found that WhatsApp is the preferred social networking site among Malaysian student.…”
Section: Discussionmentioning
confidence: 87%
“…Cankaya and Yunkul (2018) found in their study that WhatsApp is the most used social networking sites by participants in a mixed method study. Similarly, Abdulla (2017) also discovered that among other social networking sites like Twitter, Instagram, and Facebook, WhatsApp is the most preferred by university students. Besides, Ling (2016) and Yin (2016), both studies carried out in Malaysia found that WhatsApp is the preferred social networking site among Malaysian student.…”
Section: Discussionmentioning
confidence: 87%
“…Designers need to study the usage as well as the devices that the users are connected to. The connection of data services on smartphones (Desmal, 2017) has led to an exponential increase in the capabilities offered by social media platforms. To illustrate by example, users on Facebook typically access the application through their mobile phones (96%) as compared to their computers (25%).…”
Section: Influence Of Media Formats On Usagementioning
confidence: 99%
“…Empirical studies such as Desmal (2017), Peiro-Velert et al (2015) and Muhingi et al (2015) maintain that there is use of social media among student following the advent of smartphones and internet connection. However, there have been mixed reactions from academics and researchers with regard to the impact of social networks and how they affect academic performance.…”
Section: Problem Statementmentioning
confidence: 99%
“…A similar finding was found in Kenyan where Kiplagat and Ombiro (2017) noted that students access the internet and social media sites and the frequented sites were Facebook, Whatsapp, twitter, Instagram and YouTube. The most popular social media sites often used by students have been identified by empirical studies to include Whatsapp and Facebook (Desmal, 2017;Mingle, 2016;Mingle & Adams 2015;Kashif, 2013;Alwagait et al, 2014;Othman et al, 2017). Other studies such as Alwagait et al (2014) also observed twitter is also emerging as a dominant social media site used by students.…”
Section: Literature Review 21 Social Media Sitesmentioning
confidence: 99%
See 1 more Smart Citation